2014
DOI: 10.1016/j.bbrc.2014.04.114
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin is partially associated with exosomes in mouse serum

Abstract: Previous studies suggest that adipocyte-derived exosomes play a role in cell-to-cell communication during the development of metabolic diseases. However, the characteristics and function of exosomes released from adipocytes in vivo remain to be elucidated. Clearly, exosomes released from adipocytes could exist in the circulation. In addition, because the composition of exosomes is heterogenic, depending on the cellular origin of the exosome, adipocyte-derived exosomes could be accompanied by molecules produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 60 publications
6
63
0
Order By: Relevance
“…Very recently, Phoonsawat et al . also reported adiponectin‐positive EV in mouse plasma. These data indicate that adipocyte EVs are present in plasma and may therefore be systemic communicators between AT and liver or skeletal muscle.…”
Section: Resultsmentioning
confidence: 74%
“…Very recently, Phoonsawat et al . also reported adiponectin‐positive EV in mouse plasma. These data indicate that adipocyte EVs are present in plasma and may therefore be systemic communicators between AT and liver or skeletal muscle.…”
Section: Resultsmentioning
confidence: 74%
“…EVs could be successfully purified by differential centrifugation of conditioned medium obtained from cultured adipose tissue explants [15,37] or adipocyte cultures [46]. In addition, EVs obtained from mouse serum [51], differentiated 3T3-L1 cell lines [17], and rat primary adipocyte cultures [40] were found to contain fat-cell specific proteins such as aP2 and adiponectin, suggesting that mature adipocytes can contribute to EVs in circulation. Hence, secretion of EVs may be a novel means through which adipocytes communicate with distant organs and regulate whole-body metabolism under both physiologic and pathophysiologic conditions [31].…”
Section: Extracellular Vesiclesmentioning
confidence: 96%
“…Exosomes are membrane vesicles that carry a cargo of proteins, lipids and nuclear acids, which may differ based on adipogenic stages and/or under pathological conditions [120,121,122]. Adipocyte-secreted exosomes are demonstrated to contain specific transcripts (such as adiponectin [123] and aP2 [124]) and miRNAs [119,99], which are transported into recipient cells and are involved in modulating gene expression as well as energy metabolism. Several studies demonstrated that adipocyte derived exosomes mediate cell-cell communication that might play a role in controlling lipogenesis and cell size [121], obesity related disease [120] and nonalcoholic fatty liver disease [125].…”
Section: Excessive Adipose Tissuementioning
confidence: 99%